Factors Associated With The Incidence Of Sectio Caesarea In Labouring Mothers At Ummi Hospital Bengkulu Year 2024 - Charolin, Charolin; Situmorang, Ronalen; Saputri, Meita Tria (Universitas Dehasen Bengkulu, 2025)
Data from the World Health Organization (WHO) in 2021, the incidence of caesarean section worldwide increased to 21%. In Indonesia, vaginal delivery reached 81.5% and caesarean section 17.6%. In Bengkulu Province in 2023, 64% of deliveries were carried out by CS, 36% were normal deliveries. The most common CS action in Bengkulu City is 45%, and at Ummi Bengkulu Hospital, the incidence of caesarean sections has increased in the last 3 years. This type of research is quantitative with a longitudinal study method (Nursalam, 2016). The population of this study was all mothers giving birth at Ummi Bengkulu Hospital from January-December 2023 and January-June 2024, totaling 4586 people. The case sample was mothers giving birth with caesarean section due to indications of complications. Calculation of secondary data samples, calculation of total samples using the g-power calculation concept of 1293 respondents. From the caesarean section prevalence test, it is known that the number of caesarean section prevalence is 23.59% with a 95% CI range of 21.35-25.98. These results indicate that the number of caesarean sections at RSU Ummi Bengkulu from 2023-26 July 2024 was 305. This shows that the prevalence of caesarean sections is relatively high. There is a significant conclusive relationship between caesarean sections at RSU Ummi Bengkulu: preeclampsia (OR 6.55, 95%: 1.19-35.9, p-value: 0.025), premature rupture of membranes (OR: 9.81, 95%CI: 1.02-94.60, p-value: 0.0297) and fetal distress (OR: 1516.63, 95%CI: 588.5-3908.5, p-value: 0.0001). The researcher suggests that RSU Ummi Bengkulu collaborate with various parties to reduce indicators related to the occurrence of caesarean section, which is known to cause maternal and infant death, in order to reduce the incidence of AKI. This study is also a reference material that can be used as information media to conduct research development that has the same research outcomes. Expansion of the use of covariate variables to see the causal relationship of independent variables that are connected to dependent variables so that the dominant factor of caesarean section is known.